2009
DOI: 10.1111/j.1365-2966.2009.14927.x
|View full text |Cite
|
Sign up to set email alerts
|

A systematic description of shocks in gamma-ray bursts - I. Formulation

Abstract: Since the suggestion of relativistic shocks as the origin of gamma-ray bursts (GRBs) in the early 1990s, the mathematical formulation of this process has stayed at a phenomenological level. One of the reasons for the slow development of theoretical works has been the simple power-law behaviour of the afterglows hours or days after the prompt gamma-ray emission. It was believed that they could be explained with these formulations. Nowadays, with the launch of the Swift satellite and implementation of robotic gr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 117 publications
(162 reference statements)
0
18
0
Order By: Relevance
“…Observations of thousands of gamma-ray bursts and their afterglows by Swift, Fermi, Konus-wind, and other high energy satellites and ground based robotic telescopes have demonstrated that the main component in the prompt gamma-rays and their afterglows in lower energies is synchrotron emission generated in relativistic or mildly relativistic shocks. In this section we first briefly review a phenomenological shock and synchrotron emission formalism developed in [126,127]. Then, we use it to analyse both prompt gamma-ray and afterglows of GW/GRB 170817A.…”
Section: Analysis and Modeling Of Gw/grb 170817a Datamentioning
confidence: 99%
See 4 more Smart Citations
“…Observations of thousands of gamma-ray bursts and their afterglows by Swift, Fermi, Konus-wind, and other high energy satellites and ground based robotic telescopes have demonstrated that the main component in the prompt gamma-rays and their afterglows in lower energies is synchrotron emission generated in relativistic or mildly relativistic shocks. In this section we first briefly review a phenomenological shock and synchrotron emission formalism developed in [126,127]. Then, we use it to analyse both prompt gamma-ray and afterglows of GW/GRB 170817A.…”
Section: Analysis and Modeling Of Gw/grb 170817a Datamentioning
confidence: 99%
“…The phenomenological model of [126,127] assumes that GRB emissions are synchrotron/self-Compton produced by accelerated charged leptons in a dynamically active region in the head front -wake -of shocks between density shells inside a relativistic jet for prompt and with surrounding material for afterglows in lower energies. In addition to the magnetic field generated by Fermi processes in the active region, an external magnetic field precessing with respect to the jet axis may contribute in the production of synchrotron emission.…”
Section: Phenomenological Formulation Of Relativistic Shocks and Syncmentioning
confidence: 99%
See 3 more Smart Citations